Hyperautomation: The Next Frontier in Business Process Transformation - Venkataarangam, Meenu Vimala (International Journal of Computing and Engineering, 2025)
This article investigates the emerging concept of hyperautomation, which represents a comprehensive approach to business process transformation through the strategic integration of multiple advanced technologies. Hyperautomation extends beyond traditional automation by combining artificial intelligence, machine learning, robotic process automation, and intelligent business process management systems to create an ecosystem where processes are not only automated but continuously improved. The article examines the fundamental principles of hyperautomation, its technological components, implementation methodologies, organizational impacts, and challenges organizations face during adoption. By orchestrating various technologies into a cohesive automation fabric, hyperautomation enables end-to-end process optimization that spans departmental boundaries and creates seamless workflows across previously disconnected operational domains. It suggests that hyperautomation represents a paradigm shift in operational efficiency, delivering benefits across multiple dimensions, including enhanced operational performance, improved customer experiences, workforce transformation, increased organizational agility, and data-driven decision making. When strategically implemented, hyperautomation can fundamentally transform organizational capabilities and competitive positioning in the digital economy.